Improvements in thin film CdTe back contact and interface layers through sputter deposition of metals and semiconductor materials - Kindvall, Anna, author; Sampath, Walajabad, advisor; Kephart, Jason, committee member; de la Venta, Jose, committee member (Colorado State University. Libraries, 2019)
The photovoltaic industry has grown at an average annual rate of 50% over the last ten years. In that time, solar module prices have dropped significantly, with the current levelized cost of electricity averaged at $0.03 per kilowatt hour. Cadmium telluride (CdTe) photovoltaics are a common commercially produced thin-film solar cell. The leader in CdTe module production and research and development is First Solar. First Solar has set the record for research scale CdTe devices, achieving an efficiency of 22.1%, far from the theoretical limit. Improving interface layers has been identified as one of the key strategies towards further improving device performance. The focus of this study is on back contact interface layers. This research explores sputtered molybdenum oxide (MoOₓ) and molybdenum nitride (MoNₓ) thin films as alternative back contact to carbon and nickel paint in a polymer binder. The MoOₓ and MoNₓ films were characterized using resistivity measurements, Hall measurements to determine carrier concentrations, x-ray photoelectron spectroscopy to determine nitrogen and oxygen incorporation into the film and x-ray diffraction to determine crystallinity. Devices were fabricated using different compositions of molybdenum, molybdenum oxide, and molybdenum nitride with an aluminum capping layer as back contacts. This structure resulted in performances very similar to the baseline with carbon and nickel paint, proving it to be a viable alternative. Additionally, this research study explored the option of zinc telluride (ZnTe) as a buffer layer between the CdTe and metal back contact. Copper doping assists in the CdTe device performance, however too much copper can be detrimental to device performance. The ZnTe layer allows for better valence band alignment and limits copper diffusion. The device structure with ZnTe resulted in a 17.6% device, which is comparable to the baseline structure. Early results indicated devices with ZnTe were more stable and robust over time.
Keywords: CdTe photovoltaics